Agribusiness Incubator at ICRISAT : India Case Study - World Bank (Washington, DC, 2014)
The agribusiness incubator in the state of Andhra Pradesh in India is the result of a partnership between the Indian government and an international crop-research organization that is a member of CGIAR, a global partnership of organizations seeking a food-secure future. As the incubator has developed, it has become relatively independent of its founders, the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and the Indian government s Department of Science and Technology. From supporting small businesses that can bring new agricultural research and technology to market, ABI has become an incubator of incubators, and is now helping African incubators follow its model.